A chlorogenic acid-phospholipid complex ameliorates post-myocardial infarction inflammatory response mediated by mitochondrial reactive oxygen species in SAMP8 mice. (April 2018) - Li, Yi; Ren, Xuecong; Lio, Chonkit; Sun, Wenxia; Lai, Ke; Liu, Yuan; Zhang, Zhifeng; Liang, Jie; Zhou, Hua; Liu, Liang; Huang, Hui; Ren, Jing; et al.
Graphical abstract: Abstract: Mitochondrial reactive oxygen species (mtROS) directly stimulate the inflammatory cytokines cascades and participate in age-related changes of cardiovascular diseases. Application of small molecule targeting the mtROS is significant towards development of better therapy to combat inflammatory response after myocardial infarction (MI) in the aging heart. Chlorogenic acid (CGA) is a well-known natural compound while the clinical potential is largely stifled by its poor oral absorption. In the present study, we tested the protective effect of a novel chlorogenic acid-phospholipid complex (CGA-PC) against acute post-MI inflammation in aged senescence accelerated mouse model. 10-month-old SAMP8 mice were treated with CGA-PC (equivalent of CGA 10 or 20 mg/kg body weight) or phospholipid randomly by gavage on a daily basis for 2 weeks. mtROS, lipid peroxidation, H2 O2 production and oxygen consumption were evaluated in hearts subjected to ischemia reperfusion (I/R) induced by left anterior descending artery ligation. CGA-PC significantly reduced pro-inflammatory cytokines and myocardial necrosis, accompanied by decreased oxidative stress and mitochondrial respiratory deficits. p-JNK, MnSOD and soluble cytochrome c were up-regulated in the necrotic heart tissue, while CGA-PC treatment increased the expression of MKP-1 and inhibited the downstream activation of JNK. Our study indicated that CGA-PC ameliorated post-MI inflammatory response in aging heart and that it might be a promising candidate for the clinical development of CGA.